Análise espaço-temporal de prevalência de casos de Hepatite B e C no Estado do Pará - PAIXÃO, Ana Consuelo Portilho (2022)
Demonstrating a vast socio-spatial structuring, the present study is based on an observational, descriptive-analytical, ecological design of a historical series with temporal analysis corresponding to the period from 2018 to 2020 of the detection of cases of Hepatitis B and C in the state of Pará. Considered as systemic infectious diseases, they affect mainly the adult population, being mostly women in hepatitis B cases and men in hepatitis C cases. The state of Pará has specific spatial characteristics for each hepatitis analyzed, from cases concentrated in more and less populated mesoregions, due to the vector of virus dissemination. Based on this information, the work carried out a spatial-temporal and sociodemographic analysis of hepatitis B and C cases in the state of Pará, in the period from 2018 to 2020, analyzing the behavior of the virus in each mesoregion of Pará, producing thematic cartography based on confirmed cases of hepatitis B and C. Information was provided from the Central Laboratory of the state of Pará (LACEN-PA), in addition to data collection for cartographic base of the studied area from the Brazilian Institute of Geography and Statistics (IBGE), then the collected data were separated between "Detectable" and "Undetectable" cases and performed prevalence calculation for each municipality in the state and later made the union of the tables in Qgis 3.22.5 Software to generate the prevalence maps by mesoregion. The location maps, prevalence maps, map collection and Kernel maps were built using the Qgis 3.22.5 software. Tables with sociodemographic data were constructed with four analyzed classes, being "Gender", "Age", "Race/Color" and "Zone" from Excel 15.0 software. There were confirmed in the period from 2018 to 2020, 2066 reported cases of hepatitis B and 1620 reported cases of HCV. The concentration of hepatitis B cases are among people aged between 30 and 39 years of brown race, predominantly Female, and the mesoregions most affected Are the Southeast Paraense and Lower Amazon. Hepatitis C cases were largely reported among Men aged 50 to 59 years of brown race, and the mesoregions that obtained the highest prevalence rate are Metropolitan Belém and Northeast Paraense. The geoprocessing techniques proved essential to this study, allowing the construction of cartographic products for spatial-temporal analysis of events in public health to contribute to planning and actions of interest to the population.